Pengaruh Kepemimpinan Kepala Sekolah Terhadap Pelayanan Publik di Moderasi Budaya Kerja pada SMAS Dharma Pertiwi - Setiawan, Budi (Sosial Horizon: Jurnal Pendidikan Sosial, 2024)
The correlation of leadership styles in the public service that will be modernized by a work culture is essential to know and study which are the objectives of this research. There was a gap between the schools where the teacher, the head of the school, and the students are self- employed. Because the information technology provided has not been fully utilized. In this study, a random sampling system of 60 people was used for descriptive methods. Data collected through a questionnaire with a likert scale. Moderate regression analysis was performed using SPSS version 29. The results of the research show that the ownership of the head of the school with the public service can have a negative impact, with a value of sig. 0,024 < 0,05. And a work that becomes a variable of moderation between the head and public service leadership can strengthen the relationship with the value of sig. 0,013 < 0,05. Then, all variables contributed 44.1 percent to public service, with other variables not tested contributing 55.9 percent.